If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + 3)(3x + -2) = 5(3x + -2) Reorder the terms: (3 + x)(3x + -2) = 5(3x + -2) Reorder the terms: (3 + x)(-2 + 3x) = 5(3x + -2) Multiply (3 + x) * (-2 + 3x) (3(-2 + 3x) + x(-2 + 3x)) = 5(3x + -2) ((-2 * 3 + 3x * 3) + x(-2 + 3x)) = 5(3x + -2) ((-6 + 9x) + x(-2 + 3x)) = 5(3x + -2) (-6 + 9x + (-2 * x + 3x * x)) = 5(3x + -2) (-6 + 9x + (-2x + 3x2)) = 5(3x + -2) Combine like terms: 9x + -2x = 7x (-6 + 7x + 3x2) = 5(3x + -2) Reorder the terms: -6 + 7x + 3x2 = 5(-2 + 3x) -6 + 7x + 3x2 = (-2 * 5 + 3x * 5) -6 + 7x + 3x2 = (-10 + 15x) Solving -6 + 7x + 3x2 = -10 + 15x Solving for variable 'x'. Reorder the terms: -6 + 10 + 7x + -15x + 3x2 = -10 + 15x + 10 + -15x Combine like terms: -6 + 10 = 4 4 + 7x + -15x + 3x2 = -10 + 15x + 10 + -15x Combine like terms: 7x + -15x = -8x 4 + -8x + 3x2 = -10 + 15x + 10 + -15x Reorder the terms: 4 + -8x + 3x2 = -10 + 10 + 15x + -15x Combine like terms: -10 + 10 = 0 4 + -8x + 3x2 = 0 + 15x + -15x 4 + -8x + 3x2 = 15x + -15x Combine like terms: 15x + -15x = 0 4 + -8x + 3x2 = 0 Factor a trinomial. (2 + -3x)(2 + -1x) = 0Subproblem 1
Set the factor '(2 + -3x)' equal to zero and attempt to solve: Simplifying 2 + -3x = 0 Solving 2 + -3x = 0 Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -3x = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -3x = 0 + -2 -3x = 0 + -2 Combine like terms: 0 + -2 = -2 -3x = -2 Divide each side by '-3'. x = 0.6666666667 Simplifying x = 0.6666666667Subproblem 2
Set the factor '(2 + -1x)' equal to zero and attempt to solve: Simplifying 2 + -1x = 0 Solving 2 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -1x = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -1x = 0 + -2 -1x = 0 + -2 Combine like terms: 0 + -2 = -2 -1x = -2 Divide each side by '-1'. x = 2 Simplifying x = 2Solution
x = {0.6666666667, 2}
| 5a+36=61 | | 86+84+36+x=180 | | 1-x=x+x | | 3(y-2)=y-8 | | 40=3w+5w | | 4x^2-3x+285=0 | | 42=8w-2w | | 36x^3+6x^2-6x=0 | | Tan(50)=x/121 | | 28y+4=3y^2 | | x+5=222222222222 | | 28-2m=4 | | 7x^6+x-1=0 | | 5(g-3)+2(y-2)=4 | | 1.47+1.9m=-2.1(m+2.5) | | 2.8(2.9n-1.8)=9.576+2.9n | | -6(-7x-8)+6(x-8)=-8x+7x | | 5+2n=-(-3-2n) | | 3x^2+6=4 | | 5m+38=7(-2m+2)-3m | | 2m^2-4m=48 | | -2(1+6n)=-2-8n | | 37x36/6 | | x+4-6=4-x | | 3a^2+22a=-7 | | 5x+3y-13=0 | | 2=-16t^2+40t+3 | | (12x+8y)-(4x-2y)= | | (5x-1)/3-(2x-3)/5=1 | | 6+9=7x-5 | | 6x+9=7x-9 | | 6-4x=3x+3 |